Efficacy and safety of elinzanetant, a selective neurokinin-1, 3 receptor antagonist for vasomotor symptoms: a dose-finding clinical trial (SWITCH-1). Issue 3 (30th March 2023) - Simon, James A.; Anderson, Richard A.; Ballantyne, Elizabeth; Bolognese, James; Caetano, Cecilia; Joffe, Hadine; Kerr, Mary; Panay, Nick; Seitz, Christian; Seymore, Susan; Trower, Mike; Zuurman, Lineke; et al.
Abstract : SWITCH-1 was a phase 2b study assessing the efficacy, safety, and dose-response relationship of elinzanetant, a selective neurokinin-1, 3 receptor antagonist, for the treatment of vasomotor symptoms. Elinzanetant resulted in significant and clinically meaningful improvements in vasomotor symptoms, sleep and quality of life and was well tolerated across all doses. Abstract: Objective: Neurokinin (NK)-3 and NK-1 receptors have been implicated in the etiology of vasomotor symptoms (VMS) and sleep disturbances associated with menopause. This phase 2b, adaptive, dose-range finding study aimed to assess the efficacy and safety of multiple doses of elinzanetant (NT-814), a selective NK-1, 3 receptor antagonist, in women experiencing VMS associated with menopause, and investigate the impact of elinzanetant on sleep and quality of life. Methods: Postmenopausal women aged 40 to 65 years who experienced seven or more moderate-to-severe VMS per day were randomized to receive elinzanetant 40, 80, 120, or 160 mg or placebo once daily using an adaptive design algorithm. Coprimary endpoints were reduction in mean frequency and severity of moderate-to-severe VMS at weeks 4 and 12. Secondary endpoints included patient-reported assessments of sleep and quality of life. Results: Elinzanetant 120 mg and 160 mg achieved reductions in VMS frequency versus placebo from week 1 throughout 12 weeks of treatment. Least square mean reductions were statistically significant versus placebo at both primary endpoint time points for elinzanetant 120 mg (week 4: −3.93 [SE, 1.02], P < 0.001; week 12: −2.95 [1.15], P = 0.01) and at week 4 for elinzanetant 160 mg (−2.63 [1.03]; P = 0.01). Both doses also led to clinically meaningful improvements in measures of sleep and quality of life. All doses of elinzanetant were well tolerated. Conclusions: Elinzanetant is an effective and well-tolerated nonhormone treatment option for postmenopausal women with VMS and associated sleep disturbance. Elinzanetant also improves quality of life in women with VMS.